TAP SWITCHES - Asep Indra Gunawan; Drs. Lingga Hermanto, MMSI (Jurnal Sistem Komputer, 2005)
In this paper conducted a simple design tools such as Soft Switch system. This switch works with senttuhan, the first touch of this switch will be active (ON) and the second touch of this switch will be non-active (OFF). Operation switch, through the working circuit active components of the system dikaskada transistors, each transistor on the condition ON or OFF will enter the saturation region or the Cut-Off.The purpose of this scientific writing to provide an overview of design, including ease of operation and reliability. Understanding the operator ease of operation here requires only a relatively low operating energy is eventually able to move the actual, functioning as a relay connector and voltage breakers are very sensitive, touching on the device did not need to touch-hard but enough with the touch of a normal, ie operations switching at the touch of a relatively quite soft, it can activate the switch working. The expected result of timing differences between the touch operation by switching response in less than two seconds.